Perencanaan Strategik Pembentukan Karakter Anak Usia Dini di TK Islam Al-Irsyad Purwokerto - Wiyani, Novan Ardy (PROGRAM STUDI PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD), FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2017)
This paper is intended to obtain a description of the strategic planning process to shape the character of younger children in kindergarten Islam al-Irsyad Purwokerto. case study research method was selected and used to obtain these goals. The results showed that there are seven steps involved in strategic planning for early childhood shape the character. First, to accommodate the wishes and needs of parents based on the results of environmental monitoring process. Second, develop a vision, mission, and objectives of TK Islam that focuses on character building early childhood. Third, set the value of the character to be internalized in early childhood in kindergarten Islam. Fourth, prepare quality assurance Islamic kindergarten graduates. Fifth, organize the activities empowerment of children in kindergarten Islam towards achieving quality assurance Islamic kindergarten graduates. Sixth, develop programs and strategies for early childhood character formation towards achieving quality assurance Islamic kindergarten graduates. Seventh, develop instruments assessment program for early childhood character formation that leads to the achievement of quality assurance Islamic kindergarten graduates